Fully-integrated, bezel-less transistor arrays using reversibly foldable interconnects and stretchable origami substrates. Issue 18 (22nd April 2016) - Kim, Mijung; Park, Jihun; Ji, Sangyoon; Shin, Sung-Ho; Kim, So-Yun; Kim, Young-Cheon; Kim, Ju-Young; Park, Jang-Ung
Abstract : Here we demonstrate fully-integrated, bezel-less transistor arrays using stretchable origami substrates and foldable conducting interconnects. Abstract : Here we demonstrate fully-integrated, bezel-less transistor arrays using stretchable origami substrates and foldable conducting interconnects. Reversible folding of these arrays is enabled by origami substrates which are composed of rigid support fixtures and foldable elastic joints. In addition, hybrid structures of thin metal films and metallic nanowires worked as foldable interconnects which are located on the elastomeric joints.